The merchant wears Konstanz. Creating the image of a successful businessman in the Crown of Aragon in the 15th century - Viu Fandos, María (Reti Medievali Rivista, 2020)
The aim of this paper is to provide an accurate analysis of the fashion consumption of the Barcelonese merchant Joan de Torralba focusing on personal tastes and perception of self-identity. First, we will take into special consideration the luxury markets of the Crown of Aragon and the role played by Torralba and his equals stimulating a refined demand that was able to connect inland territories of the Crown with distant European markets. Secondly, we will concentrate on the merchant’s fashion expenses and consumption patterns in a comparative perspective with his family and taking into account the international fashion context of the 15th century.